2023
DOI: 10.1210/clinem/dgad560
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Risk of Vertebral Fractures in Patients With Mild Autonomous Cortisol Secretion

Vittoria Favero,
Cristina Eller-Vainicher,
Valentina Morelli
et al.

Abstract: Context The risk of vertebral fractures (VFx) in patients with adrenal incidentalomas (AI) and mild autonomous cortisol secretion (MACS) is debated. Objective To evaluate the VFx prevalence and incidence in patients with AI and MACS. Design Cross-sectional and longitudinal study on retrospective data. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
4
2
Order By: Relevance
“…Previous studies in patients with adrenal tumors have found increased fracture risk in individuals with higher cortisol levels. 11 , 12 , 17 In contrast to the current study, these studies did not exclude individuals with MACS. Moreover, a control group without known adrenal masses is very rare in studies of adrenal tumors.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Previous studies in patients with adrenal tumors have found increased fracture risk in individuals with higher cortisol levels. 11 , 12 , 17 In contrast to the current study, these studies did not exclude individuals with MACS. Moreover, a control group without known adrenal masses is very rare in studies of adrenal tumors.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies in patients with adrenal tumors have found increased fracture risk in individuals with higher cortisol levels . In contrast to the current study, these studies did not exclude individuals with MACS.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations